Sea Transportation Accident Analysis In Indonesia - Faturachman, Danny; Shariman, Mustafa (2012)
To understand fully that human consciousness to a higher protection of the environment, in such a way as to accidents at sea, which could harm the environment (pollution) became a significant consideration. Increased transport activity at both the national dimension of transport by land, sea, air, railroad, also have an impact on the other hand an increasing number of incidents and accidents. High case of maritime accidents in Indonesia at that time should be the concern of all parties, not only the ship owner but also Governments, relevant agencies and communities to be more active in providing information. The main causes of maritime accidents in general due to excess cargo from the set, whether the carriage of goods and people. Service users often do not even force themselves on board cruise ships even filled with the determination of origin can place on the ship. In order to integrate facilities and transportation infrastructure that meets the requirements of security and safety of Trend Analysis Transportation, for the Study of Maritime Transport Accident or regulatory systems and procedures, as well as human resources professionals to realize the full implementation of transportation services and effective and efficient. This becomes important for a system of good government which has the functions of government as a guideline for transportation services include regulatory aspects, aspects of supervision and control aspects.